2011
DOI: 10.1177/0093854811409004
|View full text |Cite
|
Sign up to set email alerts
|

Reliabilities, Validities, and Cutoff Scores of the Depression Hopelessness Suicide Screening Form Among Women Offenders

Abstract: Depression and hopelessness can be associated with negative outcomes among offenders, such as reduced treatment impact, institutional misconduct, suicide risk, and health care costs. This study evaluated the reliability and validity of the Depression Hopelessness Suicide Screening Form (DHS) among women offenders. The DHS Depression and Hopelessness scales showed good internal consistency and test-retest reliability. Convergent and discriminant validities were supported through the relationship of the DHS with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
5
0
1
Order By: Relevance
“…Self-harm is more common in jails (and in particular un-sentenced inmates; Fazel, Cartwright, NormanNott, & Hawton, 2008), and the motivations for such behaviour may differ among jail and prison inmates . Larger samples are needed to ensure that the DHS critical items perform equally well among men and women given that different norms have been suggested for the depression and hopelessness scales of the test (Kroner et al, 2011). We conducted exploratory analyses regarding sex differences in the performance of the items, and found similar sensitivity and specificity values for all models for men and women (analyses available upon request from the first author).…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Self-harm is more common in jails (and in particular un-sentenced inmates; Fazel, Cartwright, NormanNott, & Hawton, 2008), and the motivations for such behaviour may differ among jail and prison inmates . Larger samples are needed to ensure that the DHS critical items perform equally well among men and women given that different norms have been suggested for the depression and hopelessness scales of the test (Kroner et al, 2011). We conducted exploratory analyses regarding sex differences in the performance of the items, and found similar sensitivity and specificity values for all models for men and women (analyses available upon request from the first author).…”
Section: Limitations and Future Directionsmentioning
confidence: 95%
“…The DHS was designed specifically for use in correctional settings, and avoids the use of terms that are often included in screening tools (e.g. guilty) which may have ambiguous meaning for inmate populations (Kroner, Kang, Mills, Harris, & Green, 2011). The DHS consists of 39 true-false items to measure signs of depression, hopelessness and risk of suicide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing help with insurance coverage and medication, parole supervisors can help decrease suicidal ideation and behavior by identifying and referring parolees with specific mental disorders to psychiatric treatment, especially those with depression, substance use disorders, and schizophrenia (35,36). It is important to work with at-risk former offenders (37,38) and follow up with those who have expressed suicidal ideation or made a suicide attempt (39).…”
Section: Discussionmentioning
confidence: 99%
“…A third component of the measure is the 12 items associated with risk for suicide; among these are three items that assess current suicide ideation. The DHS has been found to have acceptable psychometric properties when applied to federally sentenced female offenders in Canada [19,20] where research has demonstrated that the DHS was generally equivalent to interviews and file reviews at identifying inmates with a history of self-harm.…”
Section: The Depression Hopelessness and Suicide Screening Form (Dhs)mentioning
confidence: 99%